A silicoaluminophosphate fluidized bed catalyst and its preparation method and application
By introducing new large crystalline molecular sieve and processing under hydrothermal environment, the problem of degradation of wear resistance and catalytic properties of silicon aluminophosphate fluidized bed catalyst during spray drying is solved, and a catalyst preparation with high crystallinity and high catalytic activity is achieved.
Patent Information
- Application Number
- CN202111129672.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-09-26
AI Technical Summary
The silicon-aluminophosphate fluidized bed catalyst prepared in the prior art is susceptible to erosion by acidic solutions during spray drying, resulting in a decrease in wear resistance and catalytic performance.
By introducing new large crystal molecular sieve rich in lattice defects as seeds, it collapses into tiny crystal fragments under a hydrothermal environment, disperses them in dry glue, and prepares a silicon-aluminophosphate fluidized bed catalyst through the vapor phase crystallization process to avoid the damage of the molecular sieve skeleton.
The wear resistance and catalytic activity of the catalyst are improved, the crystallinity of the molecular sieve is enhanced, the life of the catalyst is extended, and the main product selectivity is improved.
Smart Images

Figure CN115869997B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of molecular sieve catalyst preparation, and in particular to a silicoaluminophosphate fluidized bed catalyst and a preparation method thereof, as well as application of the catalyst in preparing olefins from oxygen-containing compounds. Background Art
[0002] Ethylene and propylene are important basic raw materials for modern petrochemical industry. The traditional preparation methods of ethylene and propylene rely on petroleum raw materials. Combined with the actual distribution of fossil energy in China, which is "rich in coal, poor in gas, and little oil", improving and transforming China's coal chemical production level and developing new coal chemical technology are in line with China's national security and energy strategy. The methanol-to-olefins route has attracted widespread attention because its raw materials can be obtained from synthesis gas in large quantities, cheaply and conveniently. In recent years, dozens of methanol-to-olefins (MTO) units have been put into commercial operation, and have achieved very good economic and social benefits.
[0003] The core of methanol to olefins technology is the development of molecular sieve catalysts. In the early stage, the catalysts used in methanol to olefins were mostly silica-alumina zeolite molecular sieves, such as ZSM-5, but their pore size was relatively large, the acidity was too strong, and the yield of low-carbon olefins was not high. In 1982, the United Carbide Corporation (UCC) of the United States synthesized the SAPO series of silica-alumina phosphate molecular sieves for the first time. The most eye-catching one is SAPO-34 molecular sieve, which has a chabazite-like structure, a small pore size, moderate acidity and strong hydrothermal stability. It shows excellent selectivity for low-carbon olefins in the catalytic methanol to low-carbon olefin reaction, which has attracted widespread attention from researchers from various countries.
[0004] When molecular sieves are used in industrial catalysis, it is generally not possible to use 100% of molecular sieves to prepare catalysts for industrial processes. First, the molecular sieve itself has poor cohesiveness and the particle size is too fine, making it difficult to form a catalyst directly used in industrial processes. Second, the manufacturing cost of molecular sieves is generally high. If 100% of molecular sieves are used as industrial catalysts, the cost will increase. Industrial processes generally require catalysts to have a certain shape and strength to adapt to industrial reactors. For fluidized bed reactors, since the catalyst itself is constantly circulating or turbulent in the reactor, the catalyst needs to have good wear resistance for fluidized bed reactors to meet the requirements of industrial processes. In the prior art, molecular sieves are prepared into fluidized bed catalysts, generally by directly preparing molecular sieves with binders, liquid media, etc. into suspensions, and then preparing microsphere catalyst products by shearing, drying and roasting. For example, CN101259425A and CN1341584A both use the above method to prepare molecular sieve fluidized bed catalysts. However, the activity and selectivity of fluidized bed molecular sieve catalysts prepared by the above method need to be further improved. CN101318143B aims at the problems of low wear resistance and poor catalytic performance of fluidized bed catalysts for the reaction of preparing ethylene and propylene from methanol and / or dimethyl ether, and adopts a method of modifying the binder to improve the high wear resistance of the fluidized bed catalyst. However, this method still has the problem that the acidic slurry causes a certain degree of damage to the molecular sieve structure during the preparation process of the microsphere catalyst. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a silicoaluminophosphate fluidized bed catalyst and a preparation method and application thereof. The silicoaluminophosphate fluidized bed catalyst prepared by the method of the present invention exhibits good wear resistance and high crystallinity. When used for preparing ethylene and propylene from methanol and / or dimethyl ether, the catalyst has high catalytic activity and high selectivity for the products ethylene and propylene.
[0006] The first aspect of the present invention provides a method for preparing a silicoaluminophosphate fluidized bed catalyst, comprising:
[0007] (1) mixing a second silicon source, a second aluminum source, a second phosphorus source and water to obtain a mixed solution I, mixing the mixed solution I with a seed crystal, and then preparing a dry glue; the dry glue is mixed with a binder, a matrix material and water to form a suspension III;
[0008] (2) high-speed shearing the suspension III obtained in step (1), and spray drying to obtain solid microspheres;
[0009] (3) The solid microspheres obtained in step (2) are subjected to vapor phase crystallization with an organic template and water, followed by calcination to obtain a silicoaluminophosphate fluidized bed catalyst.
[0010] Furthermore, the synthesis method of the seed crystal in step (1) is: a first phosphorus source, a first aluminum source, a first silicon source, a template and water are prepared into an initial gel mixture, stirred and aged for 1 to 24 hours, hydrothermally crystallized at 170 to 220° C. for 0.1 to 8 hours, and then solid-liquid separation is performed to obtain the seed crystal.
[0011] Furthermore, in the synthesis method of the seed crystal in step (1), in the initial gel mixture, the first silicon source is calculated as SiO2, the first aluminum source is calculated as Al2O3, the first phosphorus source is calculated as P2O5, and the molar ratio of template: SiO2: Al2O3: P2O5: H2O is (0.5~10): (0.05~3): (0.2~3): (0.2~3): (20~200).
[0012] Furthermore, in the method for synthesizing the seed crystal in step (1), the hydrothermal crystallization temperature is 190 to 210° C., and the hydrothermal crystallization time is 0.5 to 6 hours.
[0013] Furthermore, in step (1), the second phosphorus source, the second aluminum source, the second silicon source and water are mixed to obtain a mixed solution I, the second silicon source is calculated as SiO2, the second aluminum source is calculated as Al2O3, and the second phosphorus source is calculated as P2O5, wherein the molar ratio of each substance is: Al2O3:SiO2:P2O5:H2O=1:(0.05~2):(0.05~2):(10~200).
[0014] Furthermore, the mixed solution I and the seed crystals in step (1) are mixed to form a mixed solution II, wherein the seed crystals account for 1% to 30% of the dry weight of the mixed solution II. The mixture is heated to 80 to 120° C. under stirring, and the water is evaporated to obtain a dry glue.
[0015] Furthermore, in step (1), the dry glue is ground and then uniformly mixed with a binder, a base material and water to form a suspension III.
[0016] Further, in step (1), the pH value of the suspension III is 2.5 to 5.5; the solid content of the suspension III is 20 wt% to 50 wt%. Further, in step (1), the first aluminum source or the second aluminum source is independently selected from at least one of aluminum isopropoxide, pseudo-boehmite or alumina; the first phosphorus source or the second phosphorus source is independently selected from at least one of phosphoric acid, phosphate or phosphorous acid; the first silicon source or the second silicon source is independently selected from at least one of TEOS, white carbon black or silica sol.
[0017] Furthermore, in the synthesis method of the seed crystal in step (1), the template agent is selected from at least one of TEAOH, TPA, triethylamine, diethylamine or morpholine.
[0018] Furthermore, in step (1), the binder is selected from silica sol and / or alumina sol; and the matrix material is selected from at least one of clay, hydrotalcite and kaolin.
[0019] Furthermore, in the step of mixing the dry glue with a binder, a matrix material and water to form a suspension III in step (1), the weight ratio of the dry glue to the binder, the matrix material and the water is (10-30): (5-10): (5-20): (40-80).
[0020] Furthermore, in step (2), the high-speed shearing needs to make at least 90% of the particles in the suspension have an average particle size of less than 8 microns, preferably an average particle size of 2 to 5 microns.
[0021] Furthermore, in step (2), the average particle size of the solid microspheres is 50 to 90 microns, preferably 60 to 80 microns.
[0022] Furthermore, in step (2), the spray drying can be carried out by conventional methods in the art, wherein the inlet temperature is 270-300° C., the outlet temperature is 110-130° C., and the rotary atomizer speed is 8000-16000 rpm.
[0023] Furthermore, in step (3), the organic template is triethylamine and morpholine, wherein the mass ratio of triethylamine to morpholine is 1.5 to 4:1.
[0024] Furthermore, in step (3), the crystallization temperature is 140-220° C., and the crystallization time is 12-72 hours. Preferably, the crystallization temperature is 160-200° C., and the crystallization time is 24-48 hours.
[0025] Furthermore, in step (3), the mass ratio of the solid microspheres, the organic template and water is (20-30): (20-40): (30-60).
[0026] Furthermore, the gas phase crystallization described in step (3) is more specifically as follows: solid microspheres are placed at the upper part of a gas phase reactor, a mixture of an organic template and water is placed at the lower liquid phase position of the reactor, and after reacting at a crystallization temperature of 140 to 220° C. for 12 to 72 hours, the mixture is calcined at 400 to 700° C. for 3 to 6 hours to obtain a silicoaluminophosphate fluidized bed catalyst.
[0027] The second aspect of the present invention provides a silicoaluminophosphate fluidized bed catalyst prepared by the above method.
[0028] Furthermore, the catalyst includes a silicoaluminophosphate molecular sieve, preferably at least one of SAPO-5, SAPO-11, SAPO-17, SAPO-18, SAPO-34, SAPO-35, SAPO-44, SAPO-47, and SAPO-56.
[0029] Furthermore, the molecular sieve accounts for 5wt% to 80wt% of the catalyst.
[0030] Furthermore, the catalyst also includes a binder and a matrix material.
[0031] Furthermore, the relative crystallinity of the silicoaluminophosphate molecular sieve in the catalyst is 100% to 130%.
[0032] Furthermore, the attrition index of the silicoaluminophosphate fluidized bed catalyst is not more than 1.0 mass % / hour.
[0033] The third aspect of the present invention provides the use of the above-mentioned silicoaluminophosphate fluidized bed catalyst in the preparation of olefins from oxygen-containing compounds.
[0034] Furthermore, the oxygen-containing compound is preferably methanol and / or dimethyl ether, and the olefin is propylene and ethylene.
[0035] Furthermore, the reaction conditions for preparing olefins from oxygen-containing compounds include: a reaction temperature of 440 to 490°C, a mass space velocity of 4.0 to 15.0 h -1 , the reaction pressure is 0.10~0.17MPa.
[0036] Furthermore, the application employs a fluidized bed.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] (1) The inventors have found through research that the silicoaluminophosphate fluidized bed catalyst obtained by the prior art preparation method, in the process of spray drying pulping, the acidic solution environment will corrode the skeleton structure of the silicoaluminophosphate molecular sieve, not only affecting the wear resistance of the finished catalyst, but also destroying the original B acid site of the molecular sieve to a certain extent, causing the loss of B acid site, thereby affecting the performance of the catalyst. In the method provided by the present invention, the method of first forming and then crystallizing is used to avoid the degradation of the catalyst wear resistance and catalytic performance caused by the destruction of the molecular sieve skeleton. The present invention further introduces a new large crystal molecular sieve rich in lattice defects as a seed in the preparation process of the dry glue. In the process of preparing the dry glue by evaporating the solution, the large crystal molecular sieve will collapse into tiny crystal fragments under a hydrothermal environment and disperse in the dry glue, which ensures that a molecular sieve with high crystallinity can be more easily obtained during the gas phase crystallization process. The solid microspheres obtained after spray drying of the dry gel do not come into contact with the high-temperature aqueous solution during the gas phase crystallization process, so the prepared silicoaluminophosphate fluidized bed catalyst has the characteristics of high molecular sieve crystallinity and good catalyst wear resistance.
[0039] (2) The silicoaluminophosphate fluidized bed catalyst obtained by the preparation method of the present invention exhibits higher main product selectivity and longer catalyst life in the reaction of methanol and / or dimethyl ether to olefins. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The XRD diagrams of the fluidized bed microsphere catalysts obtained in Examples 2 to 6 and Comparative Examples 1 to 2 are shown. DETAILED DESCRIPTION
[0041] The specific embodiments of the present invention are described in detail below, but it should be pointed out that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims.
[0042] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.
[0043] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0044] It should be particularly noted that two or more aspects (or implementation methods) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solutions (such as methods or systems) thus formed are part of the original disclosure of this specification and also fall within the scope of protection of the present invention.
[0045] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.
[0046] In the present invention, the crystal phase of the molecular sieve is analyzed on a Bruker D8 polycrystalline X-ray diffractometer (XRD), a graphite monochromator, a Cu-Ka ray source (Kα1 wavelength λ=0.15406nm), a scanning angle 2θ of 5-50°, and a scanning rate of 1° / min.
[0047] In the present invention, the samples were subjected to XRD measurement under the same test conditions. The better the crystallinity of the sample, the stronger the corresponding XRD characteristic diffraction peak. The sample of Comparative Example 1 was taken as having a crystallinity of 100%, and the relative crystallinity of other samples was calculated.
[0048] In the present invention, the wear index determination method is as follows: on a VINCI Technologies D5757-11 abrasion tester, weigh 50.0 g of microsphere catalyst and load it into the abrasion tester, control and adjust the air feed pressure (adjusted pressure) to 2.0 bar (gauge pressure), the working flow rate is about 10 L / min (under standard conditions), and start timing at the same time, blow and grind for 1 hour, stop the air, remove the powder collection system, weigh its mass to an accuracy of 0.01 g, then reinstall the powder collection system on the instrument, continue blowing and grinding for 4 hours, stop the air, remove the powder collection system, and weigh its mass to an accuracy of 0.01 g. The wear index w, expressed as mass fraction per hour (% / h), is calculated according to formula (1):
[0049]
[0050] Where: m5 is the mass of the powder collection system after 5 hours, in grams (g);
[0051] m1——the mass of the powder collection system after 1 hour, in grams (g);
[0052] m——the numerical value of the sample mass, in grams (g);
[0053] m0 is the mass of the powder collection system before testing, in grams (g).
[0054] [Example 1]
[0055] 12.1 g of γ-Al2O3 and 35.0 g of deionized water are mixed evenly to form a mixed solution a; 23.3 g of orthophosphoric acid (85% by weight) and 37.5 g of deionized water are mixed evenly to form a solution b; a and b are mixed and stirred at room temperature for 2 hours to form a mixed solution c; while stirring, 31 g of triethylamine, 4.5 g of silica sol and 27.0 g of deionized water are added to c in sequence, and after sufficient stirring, an initial gel mixture for synthesizing SAPO-34 molecular sieve is obtained; wherein the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the phosphorus source is calculated as P2O5, and the molar ratio of template: SiO2: Al2O3: P2O5: H2O is 3: 0.3: 1: 1: 55. The mixture is crystallized at 200°C for 4 hours, taken out and quenched, and a seed crystal is obtained after solid-liquid separation.
[0056] [Example 2]
[0057] Under stirring, 23g of 85% phosphoric acid and 28.2g of silica sol with 30% SiO2 content were added to 94g of deionized water, and after being fully mixed, 14.6g of alumina was added. At this time, the molar ratio of each component added was Al2O3: P2O5: 1.25SiO2: 75H2O. After stirring at room temperature for 24 hours, 3.0g of the seed crystal obtained in Example 1 was added, and the temperature was gradually increased to 80°C. Stirring was continued for 3 to 5 hours. As the water evaporated during the reaction, the viscosity of the system gradually increased and became a colloid. The colloid was put into an oven and heated at 120°C for more than 12 hours, and the water was completely evaporated to become a dry colloid.
[0058] The dry glue was ground into powder, and the raw materials were weighed according to the ratio of 20% (mass) dry glue powder, 13% (mass) kaolin, 7% (mass) aluminum sol, and 60% (mass) deionized water. Except for water, the raw material ratios here are all dry basis mass ratios. The following operations were performed: first, the weighed dry glue powder and deionized water were mixed, stirred for 1 hour, and fully stirred; after high-speed shearing with a high-speed shearing machine for 15 minutes, aluminum sol was added, stirred rapidly for 15 minutes, and sheared with a high-speed shearing machine for 15 minutes; kaolin was added and stirred for 30 minutes, and a suspension was obtained after reaching a uniform state. The obtained suspension was subjected to high-speed shearing with a high-speed shearing machine for 45 minutes to obtain a suspension before spray drying, with a pH of 4.5. The particle size of the suspension was measured by a laser particle size analyzer, and the average particle size was 3.6 microns. The suspension was spray-dried at an inlet temperature of 290°C, an outlet temperature of 130°C, and a rotary atomizer speed of 15000rpm. Solid microspheres were obtained, and the average particle size of the solid microspheres was 80 microns.
[0059] 9.0g of solid microspheres were placed on the upper part of the reactor, and the lower part of the reactor was a mixed solution consisting of 7.5g of a composite template agent with a mass ratio of triethylamine to morpholine of 3:1 and 15g of water. After the reactor was sealed, it was crystallized at 180°C for 48 hours. After cooling, the obtained product was fully washed and filtered, dried at 120°C for 5 hours, and calcined at 550°C for 6 hours to obtain a silicoaluminophosphate fluidized bed catalyst. The molecular sieve in the catalyst accounted for about 40-50wt%.
[0060] [Example 3]
[0061] The steps and conditions of Example 2 were followed, but during the preparation of the dry gel, the amount of seed crystal added was 5 g. The molecular sieve in the catalyst accounted for about 40-50 wt%.
[0062] [Example 4]
[0063] The steps and conditions of Example 2 were followed, but the amount of seed crystal added during the preparation of the dry gel was 8 g. The molecular sieve in the catalyst accounted for about 40-50 wt%.
[0064] [Example 5]
[0065] According to the steps and conditions of Example 3, the raw materials are weighed according to the ratio of 15% (mass) dry rubber powder, 18% (mass) kaolin, 7% (mass) aluminum sol, and 60% (mass) deionized water for the spray slurry. The molecular sieve accounts for about 40-50wt% of the catalyst.
[0066] [Example 6]
[0067] According to the steps and conditions of Example 3, the raw materials are weighed according to the ratio of 25% (mass) dry rubber powder, 8% (mass) kaolin, 7% (mass) aluminum sol, and 60% (mass) deionized water for the spray slurry. The molecular sieve accounts for about 40-50wt% of the catalyst.
[0068] [Example 7]
[0069] According to the steps and conditions of Example 3, 9.0 g of solid microspheres were placed in the upper part of the reactor, and the lower part of the reactor was a mixed solution consisting of 10.0 g of a composite template agent with a mass ratio of triethylamine to TEAOH of 3:1 and 15 g of water. The reactor was sealed and crystallized at 200° C. for 36 hours. The molecular sieve in the catalyst accounted for about 40 to 50 wt%.
[0070] [Comparative Example 1]
[0071] 12.1 g of γ-Al2O3 and 35.0 g of deionized water are mixed evenly to form a mixed solution a; 23.3 g of orthophosphoric acid (85% by weight) and 37.5 g of deionized water are mixed evenly to form a solution b; a and b are mixed and stirred at room temperature for 2 hours to form a mixed solution c; while maintaining stirring, 31 g of triethylamine, 4.5 g of silica sol and 27.0 g of deionized water are added to c in sequence, and after sufficient stirring, an initial gel mixture for synthesizing SAPO-34 molecular sieve is obtained; the mixture is crystallized at 200°C for 24 hours, and the molecular sieve raw powder is obtained after solid-liquid separation, washing and drying.
[0072] The raw materials are weighed according to the ratio of 20% (mass) molecular sieve powder, 13% (mass) kaolin, 7% (mass) aluminum sol, and 60% (mass) deionized water. Except for water, the raw material ratios here are all dry basis mass ratios. The following operations are performed: first, the weighed molecular sieve and deionized water are mixed, stirred for 1 hour, and fully stirred; after high-speed shearing with a high-speed shearing machine for 15 minutes, aluminum sol is added, quickly stirred for 15 minutes, and sheared with a high-speed shearing machine for 15 minutes; kaolin is added and stirred for 30 minutes. After reaching a uniform state, a suspension is obtained, and the pH is 4.4. The obtained suspension is subjected to high-speed shearing with a high-speed shearing machine for 45 minutes to obtain a suspension before spray drying. The particle size of the suspension is measured by a laser particle size analyzer, and the average particle size is 4.2 microns. Spray-dry the suspension at an inlet temperature of 280°C, an outlet temperature of 110°C, and a rotary atomizer speed of 10,000 rpm. Fluidized bed catalyst microspheres are obtained. The molecular sieve accounts for about 40 to 50wt% in the catalyst.
[0073] [Comparative Example 2]
[0074] The steps and conditions of Example 2 were followed, but no seed crystals were added during the preparation of the dry gel. The molecular sieve in the catalyst accounted for about 40-50 wt%.
[0075] [Example 8]
[0076] The fluidized bed microsphere catalysts obtained in [Examples 2 to 6 and Comparative Examples 1 to 2] were characterized by XRD. The results are shown in Figure 1 It can be seen that the molecular sieve in the obtained fluidized bed catalyst is SAPO-34. Compared with Comparative Example 1, the SAPO-34 molecular sieve in the catalyst obtained in Examples 2 to 6 has better crystallinity. Taking the crystallinity of Comparative Example 1 as 100%, the relative crystallinity of Examples 2 to 6 is shown in Table 1.
[0077] Table 1. Relative crystallinity of examples and comparative examples
[0078] sample Comparative Example 1 Comparative Example 2 Example 2 Example 3 Example 4 Example 5 Example 6 Relative crystallinity 100% 105% 108% 112% 119% 110% 127%
[0079] [Example 9]
[0080] The fluidized bed microsphere catalysts obtained in [Example 2-7] and [Comparative Example 1-2] were evaluated in a fluidized bed. The reaction conditions were: 40 g of catalyst, pure methanol feed, reaction temperature 480°C, space velocity (WHSV) 4.0 h -1 , pressure 0.1MPa. The results are shown in Table 2.
[0081] Table 2 Catalytic performance of methanol to olefins in the examples and comparative examples
[0082]
[0083]
[0084] [Example 10]
[0085] The wear index of the fluidized bed microsphere catalyst obtained in [Example 2-7] and [Comparative Example 1-2] was measured. The results are shown in Table 2.
[0086] Table 2 Wear index of catalysts obtained in Examples and Comparative Examples
[0087] sample Wear index (mass % / hour) Example 2 0.52 Example 3 0.51 Example 4 0.61 Example 5 0.44 Example 6 0.70 Example 7 0.74 Comparative Example 1 1.22 Comparative Example 2 1.01
Claims
1. A method for preparing a silicoaluminophosphate fluidized bed catalyst, comprising: (1) mixing a second silicon source, a second aluminum source, a second phosphorus source and water to obtain a mixed solution I, mixing the mixed solution I with a seed crystal, and then preparing a dry glue; the dry glue is mixed with a binder, a matrix material and water to form a suspension III; (2) high-speed shearing the suspension III obtained in step (1), and spray drying to obtain solid microspheres; (3) treating the solid microspheres obtained in step (2) with an organic template and water through vapor phase crystallization and calcination to obtain a silicoaluminophosphate fluidized bed catalyst; The synthesis method of the seed crystal in step (1) is as follows: a first phosphorus source, a first aluminum source, a first silicon source, a template and water are prepared into an initial gel mixture, stirred and aged for 1 to 24 hours, hydrothermally crystallized at 170 to 220° C. for 0.1 to 8 hours, and then solid-liquid separation is performed to obtain a seed crystal; in the initial gel mixture, the first silicon source is calculated as SiO2, the first aluminum source is calculated as Al2O3, the first phosphorus source is calculated as P2O5, and the molar ratio of template: SiO2: Al2O3: P2O5: H2O is (0.5 to 10): (0.05 to 3): (0.2 to 3): (0.2 to 3): (20 to 200); In the synthesis method of the seed crystal in step (1), the template agent is selected from at least one of TEAOH, TPA, triethylamine, diethylamine or morpholine; In step (1), the matrix material is selected from at least one of clay, hydrotalcite and kaolin; in step (3), the organic template is triethylamine and morpholine.
2. The preparation method according to claim 1, characterized in that: In step (1), the second phosphorus source, the second aluminum source, the second silicon source and water are mixed to obtain a mixed solution I, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the phosphorus source is calculated as P2O5, wherein the molar ratio of each substance is: Al2O3:SiO2:P2O5:H2O=1:(0.05~2):(0.05~2):(10~200).
3. The preparation method according to claim 1, characterized in that: The mixed solution I and the seed crystals in step (1) are mixed to form a mixed solution II, wherein the seed crystals account for 1% to 30% of the dry weight of the mixed solution II. The mixture is heated to 80 to 120° C. under stirring, and the water is evaporated to obtain a dry glue.
4. The preparation method according to claim 1, characterized in that: In step (1), the first aluminum source or the second aluminum source is independently selected from at least one of aluminum isopropoxide, pseudo-boehmite or alumina; the first phosphorus source or the second phosphorus source is independently selected from at least one of phosphoric acid, phosphate or phosphorous acid; the first silicon source or the second silicon source is independently selected from at least one of TEOS, white carbon black or silica sol.
5. The preparation method according to claim 1, characterized in that: In step (2), the average particle size of the solid microspheres is 50 to 90 microns.
6. The preparation method according to claim 1, characterized in that: In step (2), the average particle size of the solid microspheres is 60 to 80 microns.
7. The preparation method according to claim 1, characterized in that: In step (3), the crystallization temperature is 140 to 220° C., and the crystallization time is 12 to 72 hours.
8. The preparation method according to claim 1, characterized in that: In step (3), the crystallization temperature is 160 to 200° C., and the crystallization time is 24 to 48 hours.
9. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of triethylamine to morpholine is 1.5-4:1; the mass ratio of solid microspheres, organic template and water is (20-30): (20~40):(30~60)。 10. The silicoaluminophosphate fluidized bed catalyst obtained by the preparation method according to any one of claims 1 to 9.
11. The silicoaluminophosphate fluidized bed catalyst according to claim 10, characterized in that The catalyst includes a silicoaluminophosphate molecular sieve.
12. The silicoaluminophosphate fluidized bed catalyst according to claim 11, characterized in that The silicoaluminophosphate molecular sieve is at least one of SAPO-5, SAPO-11, SAPO-17, SAPO-18, SAPO-34, SAPO-35, SAPO-44, SAPO-47, and SAPO-56.
13. The silicoaluminophosphate fluidized bed catalyst according to claim 10, characterized in that: The catalyst has an attrition index of not more than 1.0 mass % / hour.
14. Use of the silicoaluminophosphate fluidized bed catalyst according to any one of claims 10 to 13 in the preparation of olefins from oxygen-containing compounds.
15. The use according to claim 14, characterized in that: The oxygen-containing compound is methanol and / or dimethyl ether.
16. The use according to claim 14, characterized in that The reaction conditions for preparing olefins from oxygen-containing compounds include: reaction temperature of 440-490°C, mass space velocity of 4.0-15.0h -1 , the reaction pressure is 0.10~0.17MPa.
Citation Information
Patent Citations
Method for preparing high abrasion resistance strength fluid bed catalyst
CN101259425A
Method for preparing molecular sieve fluidized bed catalyst
CN101318143B
Abrasion-resisting catalyst for producing light olefin
CN1341584A
Fluidized bed catalyst and preparation method thereof
CN102335623A
Preparation method of molecular sieve fluidized bed catalyst
CN104437615A